2011
DOI: 10.1128/jcm.02127-10
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serotype Gambia with CTX-M-3 and armA Resistance Markers: Nosocomial Infections with a Fatal Outcome

Abstract: International audienceWe report two cases of bacteremia caused by the Salmonella enterica serotype Gambia in our children's hospital, with one fatal outcome. The isolates showed indistinguishable genotypes and infrequent resistance markers: CTX-M-3 extended-spectrum β-lactamase and armA methyltransferase. This is the first report of S. Gambia exhibiting CTX-M-3 and armA markers involved in serious infections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Real-time PCR rotor-gene Q 2plex (Qiagen, Germany) was used to amplify and detect Salmonella virulence gene invA [39][40][41] . The used oligonucleotide sequences specific for the detection of invA in Salmonella and Citrobacter freundii as previously used by Choudhury et al (2016) [39] , Moissenet et al (2011) [40] , and Tennant and Levine (2015) [41] are shown in Table 1.…”
Section: Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…Real-time PCR rotor-gene Q 2plex (Qiagen, Germany) was used to amplify and detect Salmonella virulence gene invA [39][40][41] . The used oligonucleotide sequences specific for the detection of invA in Salmonella and Citrobacter freundii as previously used by Choudhury et al (2016) [39] , Moissenet et al (2011) [40] , and Tennant and Levine (2015) [41] are shown in Table 1.…”
Section: Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…80-kb IncL/M plasmid bearing armA and CTX-M-3 together with sulphonamide and trimethoprim resistance determinants in France (Moissenet et al, 2011). The strains isolated from two babies in the intensive care unit of a Paris hospital in 2005 shared identical resistance profiles (resistance to cefotaxime, ceftazidime, gentamicin, tobramycin, amikacin and cotrimoxazole) and indistinguishable PFGE patterns.…”
Section: S Rrna Methyltransferases In Salmonella Entericamentioning
confidence: 99%